Multi-Morbidity in the Older Person: An Examination of Polypharmacy and Socioeconomic Status - Nwadiugwu, Martin C. (Frontiers in Public Health, 2021)
An emerging focus in clinically managing multi-morbidity in the older person is the challenge of finding appropriate paradigms that addresses socio-economic burden and the risk of polypharmacy. This challenge was examined by highlighting the need for institutional change and the need to address social causes of poor health drawing from the Commission on Social Determinants of Health (CSDH). Meaningful information from electronic health records (EHR), social prescribing and redistributive welfare policies were the three interventions explored from a person-centered perspective using the CARE (connecting, assessing, responding, and empowering) approach. Making economic policies such as direct taxation and conditional cash transfers that enable older people with long-term conditions to have access to healthcare services, are economic instruments that immediately redistribute state welfare and reduce income disparity. Decreased socioeconomic inequality and unorthodox prescriptive interventions that reduce polypharmacy will mitigate barriers to effectively managing the complexities of multi-morbidity.